2022
DOI: 10.3390/pharmaceutics14020332
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Dispersion Medium and Cryoprotectants on the Physico-Chemical Features of Gliadin- and Zein-Based Nanoparticles

Abstract: The evaluation of the physico-chemical features of nanocarriers is fundamental because the modulation of these parameters can influence their biological and in vivo fate. This work investigated the feasibility of saline, 5% w/v glucose and phosphate-buffered saline solution, as polar media for the development of nanoparticles made up of two vegetal proteins, zein from corn and gliadin from wheat, respectively. The physico-chemical features of the various systems were evaluated using dynamic and multiple light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
3
6
0
Order By: Relevance
“…Taking into account the results obtained, the Zein_HA NPs produced and freeze-dried with mannitol at 5% were selected for the subsequent studies. This result is in accordance with those previously obtained for cryoprotected zein NPs [ 36 ]. Moreover, Gagliadri et al demonstrated that the protective effect of mannitol on zein NPs could be related to its physicochemical properties, which can prevent Maillard reactions that commonly occur when subjected to freeze-drying [ 25 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Taking into account the results obtained, the Zein_HA NPs produced and freeze-dried with mannitol at 5% were selected for the subsequent studies. This result is in accordance with those previously obtained for cryoprotected zein NPs [ 36 ]. Moreover, Gagliadri et al demonstrated that the protective effect of mannitol on zein NPs could be related to its physicochemical properties, which can prevent Maillard reactions that commonly occur when subjected to freeze-drying [ 25 ].…”
Section: Resultssupporting
confidence: 93%
“…To evaluate the protective effect exerted by the cryoprotectants (5 and 10% w / v ), the redispersibility index (RDI) was calculated according to the following Equation (1) [ 36 ]: where D is the rehydrated NPs hydrodynamic diameter (Dh), and D 0 is the Dh of fresh NPs. RDI values close or equal to 100% mean that samples can be appropriately resuspended.…”
Section: Methodsmentioning
confidence: 99%
“…TEM analysis demonstrated a spherical morphology of the nanosystems, substantiating the results already published by our research team [ 49 ]. It also confirmed the absence of aggregates when the two active compounds were co-encapsulated within the protein matrix ( Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
“…The optimal sucrose concentration was found to be 10% w / v ( Fig. 1 ), similar to other published work on cryoprotection of biological materials [ [55] , [56] , [57] , [58] , [59] ]. It is believed that for a set material concentration, there is a minimum number of sugar molecules required to sufficiently disrupt interactions between the polar water molecules (by formation of water-sucrose hydrogen bonds [ 60 ]) to slow down the freezing rate, and form larger ice crystal with minimal ice-water interface wherein the materials tend to localize [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 86%